2020
DOI: 10.1186/s13256-020-02374-0
|View full text |Cite
|
Sign up to set email alerts
|

Paternity seven years after a negative post-vasectomy semen analysis: a case report

Abstract: Background: Vasectomy is one of the permanent methods of contraception; however, the risk of conception still exists. Early failure, defined as a postoperative semen analysis showing persistent motile sperm, occurs in 1 in every 250 patients. Late failure, defined as the rejoining of the severed ends of the vas deferens, occurs in 1 in every 2000 patients. Case presentation: A healthy 37-year-old British male presented to our clinic because his wife had conceived seven years after he had undergone a vasectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…On the other hand, recanalization is considered when motile sperm or rising sperm concentrations are seen after achieving azoospermia or RNMS [ 7 ]. Pregnancy due to recanalization may result from early or late failure, which occurs in 1 in 250 patients and 1 in 2,000 patients, respectively [ 7 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, recanalization is considered when motile sperm or rising sperm concentrations are seen after achieving azoospermia or RNMS [ 7 ]. Pregnancy due to recanalization may result from early or late failure, which occurs in 1 in 250 patients and 1 in 2,000 patients, respectively [ 7 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Jamieson et al (2004) [ 26 ], the cumulative probability of failure per 1,000 procedures (95% confidence interval) was 7.4 (0.2–14.6) 1 year post vasectomy and 11.3 (2.3–20.3) at 2, 3, and 5 years. In a case report, a pregnancy was reported 7 years after vasectomy and this was attributed to late recanalization [ 25 ]. In another study, paternity was reported despite negative semen analysis reports and the births occurred 1 to 5 years after vasectomy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations